PERANCANGAN INTERKONEKSI SISTEM PT. PLN (PERSERO)WILAYAH MALINAU DAN SEBUKU - Patria Julianto; Stefanli Daniel Mukin; Sabaruddin Sabaruddin (Jurusan Teknik Elektro, Fakultas Teknik, Universitas Borneo Tarakan, 2026)
To improve the quality and reliability of electricity supply in North Kalimantan, PT PLN (Persero) plans to interconnect isolated power systems into an integrated network. This study investigates the interconnection of the Malinau and Sebuku systems through a 20 kV distribution network. System modelling and power flow analysis were carried out using ETAP PowerStation with the Newton–Raphson method based on existing system data from both areas. The proposed interconnection consists of an 86.6 km overhead line from the Malinau PLTU bus to the Tujung bus using a 240 mm² AAAC conductor. The analysis was conducted under two operating scenarios, namely when both generating systems were in service and when the Sebuku generating system was out of service. Simulation results show that when both systems are in operation, the active and reactive power losses are 2,361 kW and 7,802 kVAr, respectively, with the lowest voltage of 18.961 kV. When the Sebuku generating system is out of service, a 1,200 kVAr capacitor bank is required at the end of the Sebuku feeder, while the active and reactive power losses increase to 2,991 kW and 9,719 kVAr, respectively, with the lowest voltage of 18.933 kV. These results indicate that the proposed interconnection is technically feasible for supporting electricity service improvement in the study area.